Sport Instructional Mode Based on Psychological Fitness Education Environment - Zongwei Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
With the continuous progress of sci & tech, social competition has become more intense, and the pressure on human beings has not eased with the improvement of material life. Sport education principle is Sport education that tends to the original nature. Making use of the charm of Sport, giving psychological health education, counseling, consultation and treatment to university students by means of Sport therapy, solving their psychological problems in time, alleviating their psychological conflicts and obstacles, enabling them to get rid of their psychological difficulties, restore their psychological balance, improve their self-confidence, and enhance their adaptability to society and environment and their endurance to setbacks, are the important contents of implementing comprehensive quality education in colleges and universities at present. In the assessment of the effectiveness of instructional mode, it not hard to seen that compared with the traditional psychological fitness instructional mode, the students in Sport instructional mode have improved their learning ability and compressive ability. Therefore, it is of positive significance to apply Sport instructional mode to students' psychological fitness education, which can promote the innovation of psychological fitness education.